The Iconographic Couple of St Michael as Weigher of Souls and the Protecting Virgin: A Visual Formula as a Marker and Maker of Medieval Sacred Space - Mihnea Alexandru Mihail (Religions)
This research addresses the formula linking between Michael the Archangel and the Holy Virgin in the wall paintings from fourteenth-century parish churches in the Hungarian Kingdom. This starts from the murals that join together between the figure of St. Michael in the act of psychostasis, as the weigher of souls, and Mary, with the mantle, represented with her all-embracing cloak, and it investigates the spatial implications between St. Michael and Mary.